William M. Browne correspondence - Browne, William M. (William Montague), 1823-1883.
ALS (Athens, Ga., 1866 February 20) written by Browne to W. Stuart in New York concerning the redevelopment of national political parties in the South during Reconstruction.
Confederate army officer, newspaper editor, and historian.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Stuart, W. -- active 1866 -- Correspondence; Political parties -- Southern States; Reconstruction (U.S. history, 1865-1877); United States -- Politics and government -- 1865-1869.; Historians; Army officers, Confederate; Newspaper editors